Factors affecting quality in Construction Project Life Cycle (CPLC) - Yaman, Siti Khalijah; Hassan, Padzil@Fadzil; Yusop, Nur Maisarah; Hashim, Nur E’zzati; Mohammad, Hairuddin; Abu Bakar, Hasniza (Penerbit UTHM, 2022)
Quality is among the critical element in managing a construction project. Unfortunately, according to several established documents, issues related to quality in the Malaysian construction project are still rampant. Therefore, to delve deeper into the predicament, understanding the factors affecting construction quality was deemed essential. This even more vital given the minimal number of manuscripts looking into the matter accordingly with the generic construction project life cycle (CPLC). Thus, to operationalise the initial research, a mixed methodology endeavour was selected. This by carrying out a Multi-layered Thematic Analysis (MLTA) to determine factors affecting the quality in the CPLC and questionnaire survey to validate each factor's agreement. Through the MLTA, the results show several similarities in factors, especially in the off-site phases. Whereby in the on-site phases, factors related to 4 M's (money, material, manpower, and machinery) were found to be common. Then, through the questionnaire survey, each factor's mean and median values indicate that the majority of respondents were agreed (scale of 4 to 5) with the dedicated phase of each factor. To sum up, there is evidence that different CPLC has different factors affecting construction quality. In the current form, the findings are valuable as a basis for subsequent research undertaking, e.g. focusing on the micro perspective of quality within each phase and parties involved in the construction project.